Caracterização da irradiância solar em Fortaleza no ano de 1996 - Albuquerque, José Sidou (1999)
A Station Digital Automatic Solarimetric was implemented and became operational in the Campus of Pici of the Federal University of Ceará, in 1996. The objective was obtain the data of global, visible and infrared solar irradiance in the terrestrial surface along the day. In addition, conventional meteorological data of temperature of the air, relative humidity, cloudiness, precipitation and heatstroke were used to characterize the atmosphere in Fortaleza. The solarimetric data were obtained daily, in the interval of 6 to 18 h (local time), minute to minute, for five radiometers and one pirgeometer endowed with filters of different optical windows, which cover the interval of wavelength between 0,28 mm and 2,50 mm. With this disposition, the global, visible and infrared solar irradiance were discretized easily starting from the data observed in the Station Solarimetric. The solar irradiance in the top of the atmosphere was calculated for everyday during 1996 and, starting from these results, it was obtained the fraction of irradiance which reached the terrestrial surface, after its depletion by molecular scattering, absorption for the ozone, absorption and the scattering for carbon dioxide and water vapor. The values of the global and infrared solar irradiance observed at solarimetric station of Pici were compared with solar irradiance estimated in the Earth surface and they showed good agreement, particularly in the time interval between 9 and 15 h (local time), which is the interval of larger incidence of solar radiation. However, it was observed that the values of visible solar irradiance measured at Pici Solarimetric Station are larger that corresponding estimated values. The analysis considered only clear days, that is, days were the cloudiness was minimum and there was not any precipitation. The effects of absorption and scattering by aerosols and clouds were not considered.